Thermal Design of Double Pipe Heat Exchangers - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2014)
This Excel workbook streamlines thermal design calculations for double pipe heat exchangers by automating the numerous calculations required. The user selects the liquids and inputs the inlet and outlet temperatures of both liquids, the flow rate of the tubeside liquid, and the tube diameters. It includes worksheets to calculate the following: 1. Tubeside and shellside properties 2. Tubeside heat transfer coefficient 3. Shellside heat transfer coefficient 4. Heat transfer rate, overall heat transfer coefficient, log mean temperature difference, required heat transfer area, tube length and both tubeside and shellside pressure drops.